2013
DOI: 10.1186/2193-8865-3-80
|View full text |Cite
|
Sign up to set email alerts
|

Study on the correlation between crystallite size and optical gap energy of doped ZnO thin film

Abstract: The present study reports an eco-friendly, biosynthesis of silver nanoparticles (AgNPs) using stem bark extract of Diospyros montana. Initially, the synthesis of AgNPs was confirmed by visual observation as color change. Further, the morphology of the biosynthesized nanoparticles, average size and presence of elemental silver were characterized by UV-Visible spectroscopy, scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray and dynamic light scattering spectrometer. Qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Furthermore, it is already reported that the crystallite size and lattice strain in ceramic nano oxides directly affects the energy band gap and piezoelectric properties. The higher crystallite size indicates lower energy band gap, which make these oxides more useful in semiconductors [6,9].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is already reported that the crystallite size and lattice strain in ceramic nano oxides directly affects the energy band gap and piezoelectric properties. The higher crystallite size indicates lower energy band gap, which make these oxides more useful in semiconductors [6,9].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…On the other hand iron oxide (Fe 3 O 4 ) is mainly utilized in fabrication of biosensors due to its low inherent toxicity, biocompatibility and strong paramagnetic behaviour [5]. Copper oxide has been used as a p-type semiconductor for the fabrication of electrical, photovoltaic devices, field emission devices due to its narrow band gap of 1.5 eV and high optical absorption coefficient [6]. Moreover, in TMOs the magnetic, electrical and optical properties are directly influenced by lattice strain and crystallite size [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, efforts are made to produce TM metal doped wide bandgap semiconductor exhibiting room temperature ferromagnetism (RTFM). Zinc oxide (ZnO) is II-VI wide band gap (E g ~ 3.37 eV) and large exciton binding energy (60 meV) compound semiconductor with hexagonal wurtzite structure of P6 3 mc space group [5]. Requirement of Curie temperature above room temperature (RT) and intrinsic ferromagnetism (FM), rather than the ferromagnetism because of magnetic clusters or secondary phases of dopants for spintronics application makes transition metal doped ZnO a favorable system owing to observation of RTFM in several ZnO based system including Mn-, Fe-and Co-doped ZnO [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the past years, ZnO was used as primary films for a gas sensing due to their high optical transmission and high electrical conductivity. So far, ZnO as a thin film can be used with verity of investigated application for optoelectronic, piezoelectric, and photovoltaic applications such as sensors [4], thermoelectric devices [5], catalysis [6], fuel-cell electrodes [7], dye-sensitized solar cells (DSSCs) [8], and electrochromic material for displays [9].…”
Section: Introductionmentioning
confidence: 99%